PROSPEK PENGEMBANGAN INDUSTRI KREATIF SEKTOR PERIKLANAN (ADVERTISING) di KOTA PEKANBARU - Situmorang, Yalanti; Kadir, Hainim; Setiawan, Deny (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Analysis of feasibility is required to see a picture of the feasible or not will be run like a business. Research was conducted on the creative industry sector, advertising in the city of Pekanbaru. The purpose of this Research was to determine the prospects for the development of the creative industries sector advertising in Pekanbaru. This Research uses primary data obtained directly from the respondents creative industry sector advertising in Pekanbaru. Samples of creative industry sector advertising used in this Research amounted to 32 units of business or industry and secondary data obtained from the Department of Industry and Trade of the City of Pekanbaru and Pekanbaru City Central of Statistics. The feasibility Research business development was examined using the financial aspects. Results of this Research showed that the creative industries sector advertising in the city of Pekanbaru eligible to run and has very good prospects. Four methods used for the calculation of investment feasibility analysis tool with the results of the calculation as follows: NPV (Net Present Value) of Rp. 1706220.088. And business efficiency (B/C ratio Method) of 1.3048, of IRR (Internal Rate of Return) methods obtained an interest rate of 43.66%. These results indicate that the rate of return that is greater than the prescribed rate of interest of 7.3%. While the method of Break Even Point (BEP) is reached at the level of sales of 27.328 m2 or Rp 651,607,543.00.Keywords: Analysis of feasibility, NPV, B / C ratio, IRR, and BEP